Growth and sustainability of agricultural systems: the case of Sicilian wine-growing farms. (2016) - Sgroi, Filippo; Testa, Riccardo; Tudisca, Salvatore; Trapani, Anna Maria Di; Dana, Léo-Paul
The Sicilian wine-growing sector is characterised by the presence on the one hand of many small enterprises that limit their activity to the first stage of the supply chain (field production) and on the other of few enterprises that adopt a strategy of total vertical integration, from the production to the sale of wine. The first group of enterprises operates in a competitive market and in many cases with marginal revenues that are lower than marginal costs, leading entrepreneurs to abandon the activity of grape production. The second group operates in an oligopolistic market and it is able to compete in an international market. Findings reveal that competitive advantage could be achieved lowering the production costs, so as to arrive on the market with a lower cost with respect to competitors. This strategy is particularly suitable for all those small Sicilian enterprises that operate in a competitive market and that limit their activity to the production phase.